2009
DOI: 10.1002/bit.22574
|View full text |Cite
|
Sign up to set email alerts
|

PEGDA hydrogels with patterned elasticity: Novel tools for the study of cell response to substrate rigidity

Abstract: The ability of cells to migrate in response to mechanical gradients (durotaxis) and differential cell behavior in adhesion, spreading, and proliferation in response to substrate rigidity are key factors both in tissue engineering, in which materials must be selected to provide the appropriate mechanical signals, and in studies of mechanisms of diseases such as cancer and atherosclerosis, in which changes in tissue stiffness may inform cell behavior. Using poly(ethylene glycol) diacrylate hydrogels with varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
230
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(234 citation statements)
references
References 27 publications
(28 reference statements)
3
230
1
Order By: Relevance
“…Acrylate-terminated poly(ethylene glycol) based hydrogels have attracted broad interest in a variety of applications due to their excellent tenability of chemical, mechanical and biological properties [3], [19]. PEG (poly (ethylene glycol) chains are neutral, highly mobile, and heavily hydrated in aqueous solution, making PEG-based hydrogel intrinsically resistant to protein adsorption and cell adhesion, thus providing a biological "blank slate" upon which desired bio functionality could be modified [20].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylate-terminated poly(ethylene glycol) based hydrogels have attracted broad interest in a variety of applications due to their excellent tenability of chemical, mechanical and biological properties [3], [19]. PEG (poly (ethylene glycol) chains are neutral, highly mobile, and heavily hydrated in aqueous solution, making PEG-based hydrogel intrinsically resistant to protein adsorption and cell adhesion, thus providing a biological "blank slate" upon which desired bio functionality could be modified [20].…”
Section: Introductionmentioning
confidence: 99%
“…8a). On the other hand, recent studies have suggested that cell adhesion and spread are mainly controlled by the mechanical property of the substrate (i.e., the elastic modulus) (Nemir et al 2010;Jaiswal et al 2015;Rehfeldt et al 2007). As shown in Fig.…”
Section: Effect Of Ps On Mechanical Properties Of Hydrogelsmentioning
confidence: 99%
“…The PEG chains in PEGDA molecules are neutral, highly mobile, and heavily hydrated by an aqueous solution. They also have a large exclusion volume, which makes the crosslinked hydrogel passive in terms of protein adsorption [12], [13]. In our technique, PEGDA hydrogel with arbitrarily defined patterns are polymerized on a-Si:H substrate under both light irradiation and electric field.…”
Section: B Materialsmentioning
confidence: 99%